The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/jacs.3c08249
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Sigmoidal Reaction Kinetics for Pyruvic Acid Condensation at the Air–Water Interface in Aqueous Microdroplets

Meng Li,
Christian Boothby,
Robert E. Continetti
et al.

Abstract: The chemistry of pyruvic acid (PA) under thermal dark conditions is limited in bulk solutions, but in microdroplets it is shown to readily occur. Utilizing in situ micro-Raman spectroscopy as a probe, we investigated the chemistry of PA within aqueous microdroplets in a relative humidity- and temperature-controlled environmental cell. We found that PA undergoes a condensation reaction to yield mostly zymonic acid. Interestingly, the reaction follows a size-dependent sigmoidal kinetic profile, i.e., an inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Both S/V and pH effects together contribute to the enhancement factor (referring to the ratio of sulfate production rates in microdroplets to that in the bulk solution) ranging from ∼1.56 × 10 3 to ∼1.14 × 10 4 times (Figure f). This striking size-dependent acceleration trend observed in this study agrees well with findings in early publications reported by our group and other research groups. ,,,,, Numerical calculations further highlight a significant acceleration of the photosensitized formation of atmospheric sulfate at the AWI of microdroplets under atmosphere-relevant conditions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Both S/V and pH effects together contribute to the enhancement factor (referring to the ratio of sulfate production rates in microdroplets to that in the bulk solution) ranging from ∼1.56 × 10 3 to ∼1.14 × 10 4 times (Figure f). This striking size-dependent acceleration trend observed in this study agrees well with findings in early publications reported by our group and other research groups. ,,,,, Numerical calculations further highlight a significant acceleration of the photosensitized formation of atmospheric sulfate at the AWI of microdroplets under atmosphere-relevant conditions.…”
Section: Resultssupporting
confidence: 92%
“…This striking sizedependent acceleration trend observed in this study agrees well with findings in early publications reported by our group and other research groups. 26,35,36,45,59,60 Numerical calculations further highlight a significant acceleration of the photosensitized formation of atmospheric sulfate at the AWI of microdroplets under atmosphere-relevant conditions. Before we set out to reveal the photosensitized reaction mechanism and make a comparison between reaction pathways that occur in the bulk and interface, key chemical features of HULIS were initially characterized.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Growing evidence points to reactions of VOCs with Criegee intermediates, and autoxidation reactions initiated by addition of OH to alkenes, providing rapid routes to highly oxygenated molecules (HOMs) which can accumulate in SOA particles. ,, Laboratory studies of the rates and products of such reactions and of new-particle SOA nucleation and growth, the latter in simulation chambers equipped with particle counters, are now unravelling this complicated chemistry. Sunlight-induced oligomerization of tropospherically photoactive compounds such as pyruvic acid and other α-keto acids dissolved in or at the surface of aqueous aerosol droplets is another proposed route to SOA formation supported by recent laboratory investigations. As a further illustration of the importance of interfacial chemistry in aerosols, pyruvic acid was also recently shown to undergo condensation reactions at the air–water interface of aqueous droplets, forming zymonic acid under dark conditions …”
Section: Laboratory Studies Of Atmospheric Photochemistrymentioning
confidence: 95%
“…109−112 As a further illustration of the importance of interfacial chemistry in aerosols, pyruvic acid was also recently shown to undergo condensation reactions at the air−water interface of aqueous droplets, forming zymonic acid under dark conditions. 113 Although not yet implemented directly in experiments on micrometer-scale water droplets, ultrafast transient absorption (TA) spectroscopy studies of photochemical reactions in bulk solutions can provide insights about aqueous photochemistry in atmospheric organic aerosols. Recent examples include measurements using both broadband UV−visible and timeresolved infrared (TRIR) spectroscopy of nitroaromatic compounds (nitrobenzene and nitrophenols), 114 which are important chromophores in brown carbon aerosols produced by biomass burning.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%